2022
DOI: 10.1186/s12886-022-02660-z
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography findings in three patients with Werner syndrome

Abstract: Background Werner syndrome is a rare, autosomal recessive disorder characterised by premature aging. It is a typical hereditary progeroid syndrome that can be difficult to diagnose owing to its rarity and the similarity of some of its symptoms, such as juvenile cataracts, to other common ophthalmologic conditions. Early onset of bilateral cataracts is currently used as the ophthalmological feature for Werner syndrome; however, ophthalmologists often find performing a detailed examination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Therefore, it may also be used as a diagnosis and severity marker. It was reported that patients with Werner syndrome have thinning of the retinal nerve fiber layer, ganglion cell complex, and choroidal thickness and the loss of visual field [ 61 ]. It may be useful for early diagnosis to have retinal and choroidal check-ups with the optical coherence tomography images when patients present with juvenile cataracts of unknown cause.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may also be used as a diagnosis and severity marker. It was reported that patients with Werner syndrome have thinning of the retinal nerve fiber layer, ganglion cell complex, and choroidal thickness and the loss of visual field [ 61 ]. It may be useful for early diagnosis to have retinal and choroidal check-ups with the optical coherence tomography images when patients present with juvenile cataracts of unknown cause.…”
Section: Discussionmentioning
confidence: 99%